2006
DOI: 10.2337/db06-0259
|View full text |Cite
|
Sign up to set email alerts
|

Serum Visfatin Increases With Progressive β-Cell Deterioration

Abstract: Visfatin has shown to be increased in type 2 diabetes but to be unrelated to insulin sensitivity. We hypothesized that visfatin is associated with insulin secretion in humans. To this aim, a cross-sectional study was conducted in 118 nondiabetic men and 64 (35 men and 29 women) type 2 diabetic patients. Type 1 diabetic patients with long-standing disease (n ‫؍‬ 58; 31 men and 27 women) were also studied. In nondiabetic subjects, circulating visfatin (enzyme immunoassay) was independently associated with insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
167
7
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(197 citation statements)
references
References 20 publications
20
167
7
3
Order By: Relevance
“…It has been demonstrated that plasma visfatin concentrations are inversely correlated to progressive ␤-cell deterioration in patients with type 1 or type 2 diabetes (15). The present data argue against an assumption that altered pancreatic insulin secretion has contributed to reduced plasma visfatin in GDM because insulin plasma concentrations were comparable in fasting conditions.…”
Section: Measurement Of Visfatincontrasting
confidence: 49%
“…It has been demonstrated that plasma visfatin concentrations are inversely correlated to progressive ␤-cell deterioration in patients with type 1 or type 2 diabetes (15). The present data argue against an assumption that altered pancreatic insulin secretion has contributed to reduced plasma visfatin in GDM because insulin plasma concentrations were comparable in fasting conditions.…”
Section: Measurement Of Visfatincontrasting
confidence: 49%
“…They also reported increased visfatin concentrations with worsening of glucose tolerance. Similarly, (4,5) reported increased circulating visfatin in patients with Type 2 DM, whereas another study (6) found that Type 2 diabetic patients showed decreased plasma visfatin concentrations. Circulating visfatin levels are reduced after weight loss in obese subjects (16), yet, in contrast, another study (17) found that weight loss has an increasing effect on visfatin concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…Such a hypothesis is supported by the results of Haider et al [14], who demonstrated that glucose infusion (under clamp conditions) could increase visfatin concentrations. Recently, it has also been shown that subjects with established type 2 diabetes have significantly raised visfatin levels when compared with newly diagnosed type 2 diabetic subjects [15]. These findings are of interest, as GDM, like type 2 diabetes, is characterised by relative hyperglycaemia and the metabolic defects of insulin resistance [16].…”
Section: Discussionmentioning
confidence: 97%